Integration of project-based learning into control system laboratory course for electrical engineering students - Boonsri Kaewkham-Ai (2019)
© 2019 IEEE. This article presents the findings of the integration of project-based learning (PBL) into the control system laboratory course, offered to senior level undergraduates in electrical engineering. Due to many limitations of the traditional laboratory teaching approach, the students could not apply the control techniques to real-world applications. To encourage these senior students to become active learners, effective engineering communicators, and to possess the problem solving skill in the field of control system technology amenable to the manufacturing sector, the PBL has been integrated into this course. Specifically, the assignment of constructing a physical demo, or so-called the mini-project with the programmable logic controller (PLC) was used to evaluate the effectiveness of the PBL. The mini-project was established as an open-ended task. Students were allowed to propose their ideas for creating the prototypes, i.e., the minimal viable products (MVPs). The PBL assignment was evaluated against a pre-defined scoring rubric. This new course structure has been applied for two semesters in the academic year of 2017. The students' grades, and the assessment of rubrics' criteria of the mini-project were used to compare with the students' grades in the 2016 academic year (with a traditional learning approach). It was found that the students' grades based on the new course scheme in academic year 2017 were better than those in the 2016 academic year, and the rubric's criteria assessment also showed encouraging results. This suggests the potential application of the PBL to other courses in the engineering curriculum.